COMPARISON OF EFFECT OF FULL FAT SOYBEAN AND NON FAT SOYBEANS MEALS IN BROILER DIETS ON THEIR GROWTH PERFORMANCE (FUDMA JOURNAL OF SCIENCES, 2022)
Study was conducted to compare the effect of full fat soybean and non-fat soybeans meals in broiler diets on their growth performance. A total of one hundred and twenty (120) day old mixed sex chicks purchase from a reputable farm were used for this study, which lasted for eight weeks. The birds were reared on deep litter floor pens using wood shavings as litter material. The birds were brooded in the same pen for two weeks and randomly divided into two (2) groups of 60 birds per group. Data collected were subjected to General Linear Model procedure of the statistics analysis system SAS statistical package. Statistically significant means were compared using Duncan Multiple Range Test (DMRT) Duncan. The results of the experiment carried out on the assessment of weight gain on broiler fed full - fat soybean showed that the final body weight, weight gained, average daily weight gain, total feed intake per bird and feed conversion ratio (FCR) of the birds increases significantly (p
Keywords: statistics analysis system, statistically significant, General Linear Mode, and Duncan Multiple Range Test